Glass Hybrid Nanocomposites Containing Metallic Ag–Ga Nanocrystals: Synthesis, Microstructure, and Photoluminescence. Issue 11 (1st September 2014) - Yin, Dewu; Pei, Lang; Liu, Zhen; Yang, Xinyu; McKittrick, J.
<x xml:space="preserve">Abstract</x> We present the report on the synthesis, microstructure, and photoluminescence of sodium borosilicate glass hybrid nanocomposites containing metallic Ag–Ga nanocrystals. Metallic Ag–Ga nanocrystals are incorporated into sodium borosilicate glass by sol–gel method plus a controlled atmosphere. The crystal structure of metallic Ag–Ga is identified to be of a cubic phase by means of X‐ray powder diffraction, and the metallic Ag–Ga crystals exist in sodium borosilicate glass as a solid solution. Transmission electron microscopy (TEM) analysis shows that the metallic Ag–Ga nanocrystals have spherical shape and good dispersed form in sodium borosilicate glass. The line scanning analysis confirms that these nanocrystals are composed of silver and gallium elements in scanning TEM mode, and the molar ratio of the two elements is close to 1:1. The high‐resolution TEM and selected‐area electron‐diffraction analysis further prove the crystal structure of metallic Ag–Ga nanocrystals. And on this basis, the final glass exhibits an enhanced photoluminescence intensity compared to stiff gel, which was ascribed to the surface plasmon resonance of metallic Ag–Ga nanocrystals.